Formulation of Lempuyang Essential Oil Lotion (Zingiber zerumbet (L.) Smith) as a Mosquito Repellent - Fahdi, Firdaus; Harahap , Khoirunnisa; Sari , Herviani; Iksen (Fakultas Farmasi, Universitas Surabaya, 2025)
Mosquito-borne diseases, such as malaria, pose a significant public health threat in Indonesia, with cases increasing to 400,000 in 2023. This study focuses on developing a natural mosquito repellent lotion using lempuyang (Zingiber zerumbet (L.) Smith) essential oil, known for its insecticidal properties, as a sustainable and eco-friendly alternative to synthetic repellents. The objective of this study is to formulate and evaluate a mosquito repellent lotion using lempuyang essential oil at varying concentrations (5%, 10%, and 15%) and assess its physical properties, safety, and repellent efficacy. Lempuyang essential oil was extracted via steam distillation from fresh rhizomes. Lotion formulations were prepared with different oil concentrations and evaluated for organoleptic properties, homogeneity, emulsion type, pH, spreadability, and stability. Skin irritation tests were conducted and mosquito repellent efficacy was tested using Culex sp. mosquitoes in a controlled environment. The essential oil extraction via steam distillation yielded 0.4% oil from fresh lempuyang rhizomes, producing a pale yellowish-white oil. All lotion formulations exhibited desirable organoleptic properties, homogeneity, and spreadability (5–7 cm), with pH levels (6.18–7.46) suitable for skin application. Stability tests confirmed no changes in appearance, color, or odor over four weeks. Irritation tests showed no adverse reactions, confirming the lotion’s safety. The 15% formulation demonstrated the highest mosquito repellent efficacy, providing 82.45% protection, outperforming the 5% and 10% formulations. These results highlight the 15% lempuyang essential oil lotion as a promising, natural, and safe mosquito repellent. Submitted: 23-03-2025, Revised: 16-04-2025, Accepted: 21-04-2025, Published regularly: June 2025